Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

A6 Solution

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Assignment 6 Solutions

1. B(s) + B(t) = 2B(s) + B(t) − B(s). Now 2B(s) is normal with mean 0 and variance 4s and
B(t) − B(s) is normal with mean 0 and variance t − s. As B(s) and B(t) − B(s) are independent,
it follows that B(s) + B(t) is normal with mean 0 and variance 4s + t − s = 3s + t.

2. (a)

P (Ta < ∞) = lim P {Ta ≤ t}


t→∞
∫ ∞
2
e−y /2 dy
2
= √
2r 0
= 2P {N (0, 1) > 0} = 1.

Another view is like this,

P (Tx ≤ t) = 2P (B(t) > x)


∫ ∞
2 −y 2
= √ e 2 dy
2π √xt

= 2(1 − Φ(x/ t)), t ≥ 0

taking the limit as t → ∞ yields P (Tx < ∞) = 2(1 − Φ(0)) = 1.


(b)
∫ ∞
E[Ta ] = P {Ta > t} dt
0

∫ √x −y2
To this end, P (Tx > t) = 1 − P (Tx ≤ t) = √22π 0 t e 2 dy . Since the constant factor √22π plays
no role in wether the integrated tail is infinite or finite, we leave it out for simplicity. It thus
suffices to show that ∫ ∫ x ∞ √
−y 2
t
e 2 dy dt = ∞
0 0
changing the order of integration, we re-write as
∫ ∞∫ x2 ∫ ∞
y2 −y 2
2 1 −y2
e 2 dt dy = x e 2 dy
0 0 0 y2
∫ 1
1 −y2
≥ x 2
2
e 2 dy
0 y
∫ 1
1
≥ x2 e−1/2 d
2 y
0 y
= ∞
−y 2
the second inequality is due to the fact that the decreasing function e 2 is minimized over the
interval (0, 1] at the end point y = 1.

1
3. Let M = {maxt1 ≤s≤t2 X(s) > x}. Condition on X(t1 ) to obtain
∫ ∞
1
e−y /2t1 dy
2
P (M ) = P (M |X(t1 ) = y) √
−∞ 2πt1

Now, use that


P (M |X(t1 ) = y) = 1, y ≥ x
and, for y < x,

P (M |X(t1 ) = y) = P ( max X(s) > x − y)


0<s<t2 −t1
= 2P {X(t2 − t1 ) > x − y}

4. Let X = X(s) and Y = X(t)−X(s). X and Y are independent r.v.’s. X has normal distribution
with mean µs and variance σ 2 s. Y has normal distribution with mean µ(t − s) and variance
σ 2 (t − s). So, the joint density function of (X, Y ) is
2
1 (x−µs)2 1 −
(y−µ(t−s))
fX,Y (x, y) = √ exp− 2σ2 s ∗ √ exp 2σ2 (t−s)
2πσ 2 s 2πσ 2 (t − s)
2 (y−µ(t−s))2
1 −
(x−µs)

= √ exp 2σ2 s 2σ 2 (t−s) (0.1)
2πσ 2 s(t − s)

Consider the transformation (x(s), x(t)) = h(x, y) = (x, x+y). We have that |Jh−1 (x(s), x(t))| =
1, then,

(X(s), X(t)) = (X, Y )

The joint density of (X(s), X(t)) is


2 ((x(t)−x(s))−µ(t−s))2
1 −
(x(s)−µs)

fX(s),X(t) (x(s), x(t)) = √ exp 2σ 2 s 2σ 2 (t−s) (0.2)
2πσ s(t − s)
2

You might also like